Analysis Factor Triggers Fraud And Corporate Governance On Indications of Fraudulent Financial Reporting Using the Pentagon Fraud Theory Approach - Astuti, Sri; Marita, Marita; Heriningsih, Sucahyo (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2019)
This study examines the correlation between fraud triggering factors using the Pentagon fraud theory approach and the role of corporate governance on the indication that companies conduct financial statement fraud. The trigger factors for fraud in the Pentagon fraud theory are pressure, opportunity, rationalization, competence and arrogance. The fraud studied in this study is financial report fraud. The financial statements are prepared and accounted for by management. The population in this study are all banking companies listed on the Stock Exchange in 2015-2018. Observation data consisting of 92 companies. The analysis tool used is correlation analysis. Based on the results of testing, the variable that correlates significantly with the indication of the company committing fraud is pressure and corporate governance. Financial statements are a measure of management's performance, so there is pressure from management to deliver their performance information properly. Good corporate governance (GCG) is one of the pillars of the market economic system, closely related to trust in both the companies that implement it and the business climate in a country. Governance mechanisms describe the organizational culture that builds employee ethics and motivates them to uphold ethical values. Inefficiencies in corporate governance will raise the risk of financial report fraud.